Impacts of food web structure and feeding behavior on mercury exposure in Greenland Sharks (Somniosus microcephalus) - McMeans, Bailey C.; Arts, Michael T.; Fisk, Aaron T. (Science of The Total Environment, 2015)
Benthic and pelagic food web components in Cumberland Sound, Canada were explored as sources of total mercury (THg) to Greenland Sharks (Somniosus microcephalus) via both bottom-up food web transfer and top-down shark feeding behavior. Log10THg increased significantly with δ15N and trophic position from invertebrates (0.01±0.01μg·g-1 [113±1ng·g-1] dw in copepods) to Greenland Sharks (3.54±1.02μg·g-1). The slope of the log10THg vs. δ15N linear regression was higher for pelagic compared to benthic food web components (excluding Greenland Sharks, which could not be assigned to either food web), which resulted from THg concentrations being higher at the base of the benthic food web (i.e., in benthic than pelagic primary consumers). However, feeding habitat is unlikely to consistently influence shark THg exposure in Cumberland Sound because THg concentrations did not consistently differ between benthic and pelagic shark prey. Further, size, gender and feeding behavior (inferred from stable isotopes and fatty acids) were unable to significantly explain THg variability among individual Greenland Sharks. Possible reasons for this result include: 1) individual sharks feeding as generalists, 2) high overlap in THg among shark prey, and 3) differences in turnover time between ecological tracers and THg. This first assessment of Greenland Shark THg within an Arctic food web revealed high concentrations consistent with biomagnification, but low ability to explain intra-specific THg variability. Our findings of high THg levels and consumption of multiple prey types, however, suggest that Greenland Sharks acquire THg through a variety of trophic pathways and are a significant contributor to the total biotic THg pool in northern seas.